1995
DOI: 10.1182/blood.v86.5.1887.bloodjournal8651887
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus within a malignant lymphoma lesion in the course of type II mixed cryoglobulinemia

Abstract: Hepatitis C virus (HCV) has been implicated as the major etiologic factor sustaining B-cell clonal expansion in type II mixed cryoglobulinemia (MC). A putative pathogenetic role of HCV in the development of MC-associated B-cell malignancies has also been speculated. We report for the first time the localization of HCV within a parotid non-Hodgkin's lymphoma (NHL) lesion in the course of HCV- related type II essential MC, an important step to implicate any infectious agent in the lymphomagenesis. Plus and minus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
50
2
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(57 citation statements)
references
References 37 publications
4
50
2
1
Order By: Relevance
“…Of interest, De Vita et al (1995) described, for the first time, the localizationof HCV within a parotid non-Hodgkin's lymphoma lesion in the course of MC, identifying the residual parotid epithelial cells as the site of HCV infection and replication in the NHL lesion. This demonstration of HCV tropism for salivary epithelial cells in vivo (De Vita et al, 1995), combined with the high prevalence of markers of HCV infection in our series of lowgrade lymphomas of MALT type, adds further evidence to the hypothesis of an influence of such viral infection on the pathogenesis of this specific lymphoma. During revision of the manuscript, Pioltelli et al (1996) reported a high prevalence of HCV infection in NHL not associated with cryoglobulinaemia, and emphasized a significant association with low-grade lymphomas of MALT type (36 .…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Of interest, De Vita et al (1995) described, for the first time, the localizationof HCV within a parotid non-Hodgkin's lymphoma lesion in the course of MC, identifying the residual parotid epithelial cells as the site of HCV infection and replication in the NHL lesion. This demonstration of HCV tropism for salivary epithelial cells in vivo (De Vita et al, 1995), combined with the high prevalence of markers of HCV infection in our series of lowgrade lymphomas of MALT type, adds further evidence to the hypothesis of an influence of such viral infection on the pathogenesis of this specific lymphoma. During revision of the manuscript, Pioltelli et al (1996) reported a high prevalence of HCV infection in NHL not associated with cryoglobulinaemia, and emphasized a significant association with low-grade lymphomas of MALT type (36 .…”
Section: Discussionsupporting
confidence: 73%
“…In fact, the presence of clonal B-cell populations have been documented in about a third of HCVinfected patients without cryoglobulinaemia (Franzin et al, 1995). Furthermore, we recently demonstrated the presence of HCV genomic sequences directly in lymph nodes involved with low-grade non-Hodgkin's lymphoma of MALT type (Luppi et al, 1996), suggesting that HCV infection is not necessarily restricted to epithelial tissues (De Vita et al, 1995), and that lymphocytes represent a possible viral reservoir, at least in some cases of the disease.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Several recent studies have demonstrated a consistent link between HCV and the onset of type II mixed cryoglobulinaemia. 5 Researchers have suggested that mixed cryoglobulinaemia may be associated with a high prevalence of low-grade NHL and that intermediate or high-grade lymphomas can also develop during the long-term follow-up in these patients. 6 In addition, the association between HCV infection and age in patients with lymphoma may reflect the cumulative risk of infection and the long interval of time that is hypothesized to elapse from the beginning of infection to clonal lymphoid proliferation.…”
mentioning
confidence: 99%
“…Furthermore, HCV seroprevalence is significantly increased in patients with B-cell non-Hodgkin's lymphoma (NHL) (Ferri et al, 1994), and B-cell NHL is significantly over-represented in patients with liver disease (Lombardo et al, 1993). Several groups have emphasized the likely implication of HCV in a fraction of B-cell NHLs (Ferri et al, 1994;De Vita et al, 1995). As in the case of other infectious agents involved in lymphomagenesis and largely diffused in the general population (Hussel et al, 1993;Boiocchi et al, 1995), one major question is why only a minority of patients with HCV infection and MC develop an overt lymphoma, and whether predisposing factors or early markers of such malignant evolution may be identified.…”
mentioning
confidence: 99%